Analysis of Achievement Development on Kabaddi Sports Management in Langkat Regency Year 2023 - Andini Ayu Pertiwi Sinaga; Eka Abdurrahman; Nadila Khairani (Journal Physical Health Recreation (JPHR), 2023)
The results of the research show that if the organization is good, the facilities and infrastructure are good, the training can run well, so that the training can run well. The method given by the trainer will run smoothly. Funding for Kabaddi coaching is still lacking, because it only relies on monthly fees, the coaches who train in Kabaddi coaching are experienced coaches. The training program is good, from the scheduled training program, the training program is communicated so that the implementation process can run well. The performance is quite good, it can train mental and spottivity. The conclusion is that the development of achievements in Kabaddi sports management throughout Langkat Regency is still not good. The suggestions in this research are that Kabaddi should have good organization and management, so that the planned program can run well and be coordinated, then the coaching process must be followed up and improved, because with coaching carried out in stages and continuously it will indirectly provide benefits to the parties. Langkat Kabaddi Coaching. Naturally, more and more local boys are becoming professional players.